IOT INTEGRATION IN WEB-BASED LECTURER ATTENDANCE SYSTEM TO IMPROVE ACADEMIC COMMUNICATION - Saputra, Surya Darma Hadi; Putra, Leonardus Sandy Ade; Yacoub, Redi Ratiandi (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
Effective relationships between students and lecturers are essential in supporting the Tri Dharma of Higher Education, but difficulties in communication and meetings can hinder this process. Internet of Things (IoT) technology offers a solution by enabling real-time management of lecturer attendance information. This research aims to: (1) design a website-based lecturer attendance information system, (2) test the system design on the device and information system, and (3) analyze the performance of the integrated system. The methodology used is the RD (Research and Development) method, which involves needs analysis, design, development, and system testing. The test results show that the designed system is able to provide information related to lecturer attendance well. Of the 10 samples, 7 were successfully enrolled in the database, and 6 successfully performed fingerprint matching. Data management is done well, although there are challenges such as the need for a stable network. The design of the device involved complex procedures, including WiFi configuration and fingerprint matching using a MySQL database, showing the potential for further development. This web-based IoT system can be accessed through various gadgets such as smartphones, laptops, or computers, making it easier for users to access information. Overall, this system provides a practical and efficient solution to improve communication and meetings between lecturers and students.